Relationship between Tea drinking and Bone Mineral Density in Iranian population - A Hossein-nezhad; Zh Maghbooli; AR Shafaie; E Javadi; B Larijani (Tehran University of Medical Sciences, 2007)
Background: Tea is the most commonly consumed beverage by Iranian adults after water, and while previous studies have examined the negative effects of coffee-based caffeine on Bone Mineral Density (BMD), the relationship between the consumption of tea and BMD has not been clearly explored. The aim of this study was to investigate the relationship between habitual tea drinking and BMD in the adult Iranian population. Methods: BMD was measured at the lumbar spine and hip, in 830 men and women living in Tehran, all aged between 20 and 76 yr old. The degree of tea consumption was assessed by questionnaire, and subjects were categorized as either tea drinkers (more than 5 cups of tea per day) or non-tea drinkers (equal or less than 5 cups of tea per day). Results: After adjusting for age and body mass index, it was found that female tea drinkers had a small (4.2%), but significantly higher BMD in the hip (P= 0.01). Conclusions: This may suggest a potentially positive effect for habitual tea drinking on the BMD of those women with an inadequate consumption of calcium and vitamin D.